Stress reactivity in preschool-aged children: Evaluation of a social stress paradigm and investigation of the impact of prenatal maternal stress - Send, Tabea; Bardtke, Svenja; Gilles, Maria; Wolf, Isabella; Sütterlin, Marc; Laucht, Manfred; Witt, Stephanie; Rietschel, Marcella; Streit, Fabian; Deuschle, Michael (Psychoneuroendocrinology, 2019)
Prenatal maternal stress is an established risk factor for somatic and psychological health of the offspring. A dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis in offspring has been suggested as an important mechanism. However, the impact of prenatal stress on stress reactivity in preschool-aged children is not yet well understood. This is partly due to the fact that for this age group there is no stress test as well established as for older children and adults. In the present work a previously published stress test (Kryski et al., 2011) was evaluated in a large sample of 45-month-old children (n = 339). Furthermore, the relation between measures of prenatal maternal stress and cortisol reactivity was investigated. Prenatal stress was defined as psychopathology (self-report available for n = 339; expert-rating available for a subsample of n = 246) and perceived stress (n = 244) during pregnancy. The stress paradigm elicited significant increases in salivary cortisol 30 and 40 min after the test, and 60.8% of the children were classified as responders. Lower cortisol levels after the stress test were observed in the group of children with prenatal stress defined as maternal psychopathology (both self-reported and expert-rated). Maternal perceived stress as a continuous measure was not significantly associated with cortisol levels. However, when comparing children in the highest quartile of maternal perceived stress to all other children, significantly lower cortisol values were observed in the prenatally stressed group. The present study confirms the paradigm by Kryski et al. as an effective stress test for preschool-aged children. Moreover, it provides further evidence that prenatal stress impacts HPA axis reactivity. Future studies should target the timing, nature, and intensity of prenatal stressors and their effect on the stress response in offspring at different developmental stages.
Available online 5 November 2018
Gesehen am 30.09.2019